Enhancing Public Asset Management for Inclusive Tourism: A Strategic SWOT Approach - Susanto, Eko; Rahman, Bimo Falah Abdul; Husniah, Diana; Lestari, Gita Meilia; Az Zahra, Hana Shofiyyah (Integrasi Sains Media, 2024)
This study conducts a strategic analysis to optimize public assets for inclusive tourism development in Indonesia. Amid rising global demand for accessible tourism, public assets—such as urban parks, historical landmarks, and coastal areas—offer significant economic, social, and cultural potential. However, poor infrastructure maintenance, weak regulatory enforcement, and fragmented governance hinder their effective utilization. The research applies a weighted SWOT analysis to map strategic priorities by employing a mixed-method approach that integrates expert panel discussions using the Delphi method, field surveys, structured observations, and secondary data analysis. The findings reveal that internal weaknesses and external threats outweigh strengths and opportunities, positioning Indonesia's public asset management in a defensive quadrant (WT strategy). Consequently, strategic recommendations include strengthening governance through enhanced regulatory frameworks and Good Corporate Governance (GCG) principles, leveraging smart tourism technologies, and fostering sustainable public-private partnerships (PPPs). The study concludes that by addressing these challenges through multi-stakeholder collaboration and innovative financing models, Indonesia can transform its public assets into globally competitive, inclusive tourism destinations, contributing to long-term sustainable development.